2012
DOI: 10.1002/app.38192
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of carboxymethyl sago pulp hydrogel from sago waste by electron beam irradiation and swelling behavior in water and various pH media

Abstract: Solutions of carboxymethyl sago pulp (CMSP) of various degree of substitution were irradiated with electron beam of various radiation doses. The gelation dose (D g ) and p o /q o ratio (p o is degradation density, q o is crosslinking density) is dependent on CMSP concentration and degree of substitution. In the range of concentrations of 10% to 80% (w/v) CMSP with degree of substitutions of 0.4, 0.6, and 0.8, the p o /q o ratio decreases with increasing %CMSP showing that crosslinking processes are dominating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
2
22
0
2
Order By: Relevance
“…Hence, increasing the concentration of NaOH could cause the second reaction to prevailing more than the first. According to Pushpamalar et al [25], increasing NaOH would lead to more glycolate formation. Similar research was done on maize starch where it was concluded DS value would also gradually decline due to the sodium glycolate formation in the synthesis of CMC and polymer degradation would also occur due to the high concentration of NaOH [61].…”
Section: Degree Of Substitution (Ds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, increasing the concentration of NaOH could cause the second reaction to prevailing more than the first. According to Pushpamalar et al [25], increasing NaOH would lead to more glycolate formation. Similar research was done on maize starch where it was concluded DS value would also gradually decline due to the sodium glycolate formation in the synthesis of CMC and polymer degradation would also occur due to the high concentration of NaOH [61].…”
Section: Degree Of Substitution (Ds)mentioning
confidence: 99%
“…The reaction mixture was then cooled and filtered, and the product was suspended in 300 mL of methanol and stirred using a mechanical stirrer for 12 h to remove any undesired impurities. The suspension was then neutralized with glacial acetic acid, and washed three times with 70% (v/v) ethanol and finally with 95% (v/v) ethanol, filtered, and dried at 60˝C till constant weight [25]. Approximately, 5 g of synthesized CMSC was then dissolved in 100 mL of distilled water at 80˝C with constant stirring for 10 min.…”
Section: Synthesis Of Cmscmentioning
confidence: 99%
“…1) dose from 10 to 25 kGy, indicating cross-linking predominates over scission and thus gel fraction is proportional to the applied radiation dose (Vijayabaskar et al, 2004;Thenapakiam et al, 2013). The reduction in % GF beyond 25 kGy is possibly due to more scission and oxidative degradation taking place as compared to cross-linking (Pushpamalar et al, 2013b;Thenapakiam et al, 2013). Similarly, gel fraction of 10% CMSP solution increased until 20 kGy and after that started declining at higher radiation doses.…”
Section: Preparation Of Ciprofloxacin Hcl Loaded Cmsp Discsmentioning
confidence: 80%
“…Penghasilan biobahan menggunakan teknik radiasi telah mendapat tempat dalam penyelidikan di negara ini. Pushpamalar [6] melaporkan bahawa hidrogel yang dihasilkan melalui taut silang secara radiasi telah digunakan sebagai pembalut luka untuk pesakit di Hospital Navi 411. Justeru, penggunaan sinaran gamma telah dibuktikan selamat digunakan dalam industri perubatan.…”
Section: Pengenalanunclassified